Trends and Inequities in Use of Abortion Services in Nepal: A Nepal Demographic and Health Survey Data Analysis 1996-2022 A.D. - Gautam, Manish; Mehata, Suresh; Karki, Sujan; Ghimire, Jagadishwor; Maharjan, Sanju; Dotel, Bhogendra Raj (Journal of Nepal Health Research Council, 2024)
Background: Despite policy advances and public health initiatives in Nepal to improve access to reproductive healthcare, disparities persist in utilization of abortion services. Grounded in longitudinal data from the Nepal Demographic and Health Survey from 1996 to 2022, this study aims to shed light on evolving patterns in pregnancy outcomes and inequities in use of abortion services across ecological zones and wealth quintiles. Methods: Utilizing six rounds of Nepal Demographic and Health Survey data, pregnancy outcomes were categorized as abortion, delivery, miscarriage, or stillbirth. Income-related inequality in the utilization of abortion services was assessed through the concentration index, ranging from -1 to 1. Trends over time were evaluated using the annual rate of change. Results: The ARC indicated a substantial rise in induced abortion rates, surging from 0.4% in 1996 to 8.8% in 2022. In contrast, live births witnessed a decline from 92.8% to 81.2%. Significant variations were observed across ecological zones and wealth quintiles, with the Mountain zone and the Poorest group experiencing the most pronounced increases in induced abortion rates. By 2022, the concentration index reached a near-zero value, signifying a near-elimination of income-related disparities in the use of induced abortion services. Discussion: The findings suggest that while there has been significant progress in access to and use of abortion services in Nepal, particularly post-2002 policy shifts, challenges remain. Women from lower socio-economic backgrounds continue to face barriers, indicating the need for a multi-pronged approach to address residual challenges. Conclusions: Nepal has made remarkable strides in enhancing equitable access to and use of induced abortion services, but more needs to be done to guarantee equitable access for all women. Future efforts should focus on policy reforms, infrastructural improvements, and societal change to eliminate existing barriers to reproductive healthcare. Keywords: Abortion services; concentration Index; socio-economic disparities.